Twenty Challenging Minutes to Take the Right Decision - Shetty, Dr. Priyanka P; Naik, Dr. Ramadas; Nair, Dr Vineeth G.; Sudhakar, Dr Shubha; Latheef, Dr Ali Abdul (International Journal of Innovative Research in Medical Science, 2019)
Background: The diagnostic accuracy of frozen section is an important source of information and a high risk procedure in surgical pathology. This is an important tool, not only in the management of surgical patients but also has a pivotal role in institution’s quality assurance in histopathology. Aims and objectives: To analyze indications, efficacy, accuracy, limitations, deferrals and turnaround time for all frozen sections in correlation with histopathology. Materials and methods: A retrospective analysis of all the frozen samples was done in correlation with permanent sections from June 2016 till July 2017. The diagnostic accuracy, sensitivity, specificity, turnaround time, deferrals and limitations were analysed. Results: A total of 45 specimens for frozen sections were sent to the department of Pathology during the time period. Out of these, 97.8% (n=44) were accepted and 2.2% (n=1) were deferred. Of the remaining 44 specimens, 1 (2.3%) was discordant and 43 (97.7%) were concordant to permanent diagnoses. Specimens were primarily from the ovary, breast and lymph nodes. The overall sensitivity, specificity, positive predictive value and negative predictive value of the frozen section compared to formalin fixed paraffin embedded sections (as gold standard) were 97.7%, 100%, 100% and 100% respectively. The average turn-around time for frozen section diagnosis was 23 minutes. Conclusion: Frozen section diagnosis is an efficient, rapid, reliable and highly accurate tool in surgical diagnosis and management. The multidisciplinary approach helped avoiding limitations ensuring optimal patient care.